Evaluation of murine cytomegalovirus antibody detection by serological techniques. - Anderson, C A (1983)
Naturally acquired murine cytomegalovirus (MCMV) infection in laboratory strains of mice induces antibody levels which are generally undetectable by standard techniques; therefore, MCMV has not been included routinely in mouse viral antibody screening programs. The relative sensitivity of three assay systems, the nuclear anticomplement immunofluorescence (NACIF), the enzyme-linked immunosorbent assay (ELISA), and the complement fixation (CF) test, was evaluated for the detection of MCMV antibodies. Sera were harvested from CD1 male mice (33 days old) infected intraperitoneally with salivary gland-passaged MCMV (Smith strain). The sera were assayed separately at weeks 1 through 8, and at week 11, 16, and 25 post-inoculation; a total of 167 mice in 11 groups were tested. The animals tested at 1 week post-inoculation had low levels of antibodies to MCMV as measured by the NACIF test (1:10), whereas only 25% were positive by ELISA, and none was positive by CF until 5 weeks post-inoculation. A higher titer of MCMV antibodies was measured by CF (1:640) than by NACIF (1:40) at 6 months post-inoculation; yet, a titer of 1:3,200 was detected by ELISA from the same serum. The ELISA technique was more sensitive for detecting persistent infection with MCMV, and NACIF was more useful for detecting acute MCMV infection. Since MCMV can have significant long-term effects on the immune system, it is recommended that testing for antibodies to MCMV be included in mouse viral antibody screening protocols.